1998
DOI: 10.1002/etc.5620170924
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivity of five species of macrophytes and six species of algae to atrazine, metribuzin, alachlor, and metolachlor

Abstract: Abstract-This study determined the relative sensitivity of five species of aquatic macrophytes and six species of algae to four commonly used herbicides (atrazine, metribuzin, alachlor, and metolachlor). Toxicity tests consisted of 96-h (duckweed and algae) or 14-d (submerged macrophytes) static exposures. The triazine herbicides (atrazine and metribuzin) were significantly more toxic to aquatic plants than were the acetanilide herbicides (alachlor and metolachlor). Toxicity studies ranked metribuzin Ͼ atrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(90 citation statements)
references
References 23 publications
7
78
0
3
Order By: Relevance
“…Additionally, our results support previous studies in which green algae appear very sensitive to atrazine, while cyanobacteria and diatoms appear more tolerant. Fairchild et al (1998) reported that green algae were typically more sensitive than cyanobacteria to atrazine, metribuzin, alachlor, or metolachor. Tang et al (1997) found lower EC 50 values for green algae than diatoms after several days of exposure to atrazine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, our results support previous studies in which green algae appear very sensitive to atrazine, while cyanobacteria and diatoms appear more tolerant. Fairchild et al (1998) reported that green algae were typically more sensitive than cyanobacteria to atrazine, metribuzin, alachlor, or metolachor. Tang et al (1997) found lower EC 50 values for green algae than diatoms after several days of exposure to atrazine.…”
Section: Resultsmentioning
confidence: 99%
“…A number of laboratory, microcosm and fi eld studies have examined atrazine toxicity in freshwater algae (DeNoyelles et al 1982;Herman et al 1986;Solomon et al 1996;Tang et al 1997;Fairchild et al 1998). From these studies, it is generally recognized that certain algal species are more sensitive to atrazine (DeNoyelles et al 1982;Tang et al 1997;Fairchild et al 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lemna gibba, because of it is a monocotyledon, may also possesses similar detoxifying mechanisms involving glutathione. Furthermore, some Lemnaceae species are considered tolerant to triazinic herbicides (Fairchild et al, 1998). Similar tolerance mechanisms are common amongst evolutionary close species.…”
Section: Efficiency Of Atrazine Removalmentioning
confidence: 99%
“…A behavioural effect was scored when invertebrate behaviour in treated systems deviated from controls. The measurement endpoints in the macrophyte tests were biomass, which was converted to relative growth (using the biomass at the start of the test), and photosystem II efficiency (F PSII ), an endpoint frequently used in phytoplankton testing (Fairchild et al 1998;Juneau et al 2002;Lürling and Verschoor 2003) which can also be used in macrophyte testing (Snel et al 1998). F PSII is a measure of the efficiency of the photosystem II electron flow, measured as chlorophyll fluorecence, and was sampled non-destructively by means of a mini-PAM photosynthesis yield analyzer (WALZ, Germany).…”
Section: Endpointsmentioning
confidence: 99%